RING: An integral equation algorithm for HF-VHF radio wave propagation over irregular, inhomogeneous terrain - Ott, R. H. (Radio science, 1992)
A modification in the mathematical derivation of an integral equation for propagation over irregular, inhomogeneous terrain and a numerically stable algorithm, RING, is developed to extend the frequency range of program WAGNER to frequencies in the VHF region. The solution to the integral equation is compared to residue theory and Fock theory and excellent agreement is obtained.